A novel vaccine construct against Zika virus fever: insights from epitope-based vaccine discovery through molecular modeling and immunoinformatics approaches - Alharbi, Metab; Alshammari, Abdulrahman; Alsabhan, Jawza F.; Alzarea, Sami I.; Alshammari, Talal; Alasmari, Fawaz; Alasmari, Abdullah F. (Frontiers in Immunology, 2024)
Zika virus (ZIKV) is an emerging virus associated with Flaviviridae family and mainly causing infection in pregnant females which leads to several abnormalities during pregnancy. This virus has unique properties that are concern for pathological diseases. As the virus has the ability to evade immune response and a crucial effort is required to tackle ZIKV. Vaccines are potential and safe way to control different pathogenic infectious diseases. In the current research, a multiepitope-based vaccination against the Zika virus is being designed using in silico methods. For epitopes prediction and prioritization, phase Zika virus polyprotein (YP_002790881.1) and flavivirus polyprotein (>YP_009428568.1) were targeted. The predicted B-cells epitopes were used for MHC-I and MHC-II epitopes prediction. Afterward several immunoinformatics filters were applied and total 09 (REDLWCGSL, MQDLWLLRR, YKKSGITEV, TYTDRRWCF, RDAFPDSNS, KPSLGLINR, ELIGRARVS, AITQGKREE and EARRSRRAV) epitopes were found as a probable antigenic in nature, non-allergen, non-toxic and water soluble without any toxins. Selected epitopes were joined using a particular GPGPG linker to create the base vaccination for epitopes, and an extra EAAAK linker was used to link the adjuvant. A total of 312 amino acids with a molecular weight (MW) of 31.62762 and an instability value of 34.06 were computed in the physiochemical characteristic's analysis, indicating that the vaccine design is appropriately stable. The molecular docking analysis predicted binding energy -329.46 (kcal/mol) for TLR-3 and -358.54 (kcal/mol) for TLR-2. Moreover, the molecular dynamic simulation analysis predicted that the vaccine and receptor molecules have stable binding interactions in dynamic environment. The C immune simulation analysis predicted that the vaccine has the ability to generate both humoral and cellular immune responses. As the design vaccine construct has best efficacy to evoke immune response in theory but experimental analysis is required to validate the in silico base approach and ensure its safety.